Prerequisites for Emergency Laparoscopic Surgery for Colorectal Cancer - Young Wan Kim (Journal of Surgery Proceedings, 2016)
This practical overview lists prerequisites for emergent laparoscopic colorectal cancer surgery, including team readiness, equipment, and perioperative protocols to optimize patient safety.
Keywords: Emergencies